Design and performance of optical cross-connects with limited wavelength conversion - Chai, Teck Yoong (2008)
Wavelength conversion can maximize wavelength reuse and boost the efficiency of wavelength-routed WDM all-optical networks but it is both costly and impractical to employ wavelength conversion extensively throughout the network. On the other hand, limited wavelength conversion is capable of improving the efficiency.